PERSPEKTIF BISNIS : KAJIAN LINGKUNGAN EKSTERNAL DAN LINGKUNGAN INTERNAL PEMANFAATAN LIMBAH LIDI KELAPA SAWIT DI KABUPATEN ROKAN HILIR PROVINSI RIAU - Rosmayani Rosmayani; Annisa Mardatillah (Program Pascasarjana Universitas Riau, 2022)
Palm oil is one of the largest agricultural commodities in Indonesia, which positively influences economic and social growth. Riau Province is the province with the largest oil palm plantation in Indonesia. Economic development is considered a threat because it pursues growth alone and is considered to ignore environmental conditions. So far, palm oil waste has been used for solid waste as briquettes, biogas, paper pulp raw materials, and liquid waste as fertilizer. Meanwhile, palm oil sticks are considered commercial and can become a new industry but have not been developed. The purpose of this study was to examine from a business perspective the external and internal environment in the utilization of palm oil stick waste in Rokan Hilir district, Riau Province. The method used in this research is descriptive qualitative. The results showed that the external environment consisted of guidance from the government, assistance with business facilities and equipment, loan application procedures, and licensing procedures, while the internal environment consisted of business capital, human resources, business networks, technology and equipment, product promotion and online marketing/marketing.